HISTORICAL IN THE FORMATION OF MORAL THINKING IN YOUTH PLACE OF MONUMENTS: IMAM AL-BUKHARY MEMORIAL COMPLEX. (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
In this article, reconstruction works of the memorial complex of Imam al-Bukhari after independence and studying the works of Imam al-Bukhari, researching them, as well as physical and legal entities moral among young people by studying Islamic manuscripts, petroglyphs Concepts are a struggle against the dogmatic ideas of religious ekremism. Shaping our national values, on the formation of a sense of pride in contributing to the world science culture the researcher expressed his thoughts.